Jawaharlal Nehru and his political views - Martyshin Orest (Moscow Progress publishers, 1989)
Jawaharlal Nehru's political thoughts centered around advocating for a socialist, secular, and democratic India with a focus on self-reliance and modernization. He believed in the importance of science, technology, and rapid industrialization for building an independent economy. Nehru championed secularism, advocating for equal rights for all religions and ensuring secular governance. He also emphasized the welfare of marginalized groups and promoted policies for their upliftment.
Keywords: Socialism; Democracy; Modernization